Perbanyakan Fungi Mikoriza Arbuskula (FMA) Indigenous Pohon Mangga Lokal Indramayu Dari Berbagai Sumber Dan Dosis Inokulum Pada Tanaman Inang Pueraria javanica - Rusminah, Putri Shinty Charisma Yuyun; Sumarna, Pandu; Asad, Faisal Al; Laila, Fadhillah; Dwimartina, Fina (Universitas Wiralodra, 2024)
Mango fruit (Mangifera indica L.) is one of the fruits that is popular with Indonesian people because it contains quite complete vitamins and is affordable. Development of mango cultivation in Indramayu is carried out throughout the year, but mango production fluctuates at each harvest time. One of the reasons for this is alternate bearing, namely the uncertain condition of the mango harvest every year due to internal or climatic factors. One effort that can be made to control this phenomenon is by using biological fertilizers such as Arbuscular Mycorrhizal Fungi (FMA). The host plant used for AMF propagation is Pueraria javanica because it is more resistant to humidity and low temperatures compared to sorghum. This research aims to obtain a source of AMF inoculum that is suitable for vegetative growth of Pueraria javanica and the highest number of spores and to obtain the right dose for the development of AMF and growth of the Pueraria javanica host. This research used a factorial Randomized Block Design with 2 factors where the first factor was AMF Inoculum Source which consisted of three types ( Lohbener Village mango trees, Jatisawit Village mango trees, Krasak Village mango trees). The second factor is the dose of the AMF inoculum source which consists of three levels of spore number (60 g, 80 g, 100 g). The results of the study showed that there was no interaction between the inoculum source and the dose on the growth of the host plant Pueraria javanica. The inoculum source of mango trees in Krasak Village had the best influence on the number of leaves of the host plant Pueraria javanica.